Game Changers: Blockbuster Small-Molecule Drugs Approved by the FDA in 2024 - Zhonglei Wang; Xin Sun; Mingyu Sun; Chao Wang; Liyan Yang (Pharmaceuticals)
This article profiles 27 innovative advancements in small-molecule drugs approved by the U.S. Food and Drug Administration (FDA) in 2024. These drugs target various therapeutic areas including non-small cell lung cancer, advanced or metastatic breast cancer, glioma, relapsed or refractory acute leukemia, urinary tract infection, Staphylococcus aureus bloodstream infections, nonalcoholic steatohepatitis, primary biliary cholangitis, Duchenne muscular dystrophy, hypertension, anemia due to chronic kidney disease, extravascular hemolysis, primary axillary hyperhidrosis, chronic obstructive pulmonary disease, severe alopecia areata, WHIM syndrome, Niemann–Pick disease type C, schizophrenia, supraventricular tachycardia, congenital adrenal hyperplasia, and cystic fibrosis. Among these approved small-molecule drugs, those with unique mechanisms of action and designated as breakthrough therapies by the FDA represent a significant proportion, highlighting ongoing innovation. Notably, eight of these drugs (including Rezdiffra®, Voydeya®, Iqirvo®, Voranigo®, Livdelzi®, Miplyffa®, Revuforj®, and Crenessity®) are classified as “first-in-class” and have received breakthrough therapy designation. These agents not only exhibit distinct mechanisms of action but also offer substantial improvements in efficacy for patients compared to prior therapeutic options. This article offers a comprehensive analysis of the mechanisms of action, clinical trials, drug design, and synthetic methodologies related to representative drugs, aiming to provide crucial insights for future pharmaceutical development.